INFLUENCE OF ECCENTRIC TRAINING ON NON DOMINANT HAMSTRING STRENGTH IN SPRINTERS - P.SUDHESH (International Journal of Pharma and Bio Sciences, 2013)
Study focuses on muscle imbalance of non - dominant hamstring with dominant hamstring muscle of lower limb, which is one of the pre- disposing factor for injury. Moreover the injury is likely to occur in the eccentric phase ,the strength imbalance can also hinder the performance. Thereby aim of study is to determine the influence of eccentric training on Non – Dominant Hamstring Strength in Sprinters .for this a pilot study is been conducted using hoping test to find out the non- dominant leg, after differentiate the non dominant hamstring where given eccentric strengthening for the period of six weeks. Pre and post strength assessment carried out with 1 RM test. Speed test where assessed using 30 meters sprint test Result; shows significant strength and speed of the sprinters. Conclusion: the study concluded that strength training initiate greater strength in non dominant hamstring, which indirectly improve the performance of sprinters.